Review of Ti3C2Tx MXene Nanofluids: Synthesis, Characterization, and Applications - Samylingam, Ilan cheliyan; Kadirgama, Kumaran; Samylingam, Lingenthiran; Aslfattahi, Navid; Ramasamy, Devarajan; Norazlianie, Sazali; Wan Sharuzi, Wan Harun; Kok, Chee Kuang (ETASR, 2024)
MXene-based nanofluids are important because of their thermal and rheological properties, influencing scientific and industrial applications. MXenes, made of titanium carbides and nitrides, are investigated for nanofluid enhancement. This review covers MXene nanofluid creation, characterization, and application. To produce nanoscale MXene particles, two-dimensional materials are dissolved and dispersed in a base fluid. The stability and efficacy of MXene nanofluids depend on production methods, such as chemical exfoliation, electrochemical etching, and mechanical delamination. Improved heat transfer coefficients and thermal conductivity from MXene nanofluids help resolve heat transfer, energy efficiency, and thermal control problems. This extensive review also addresses long-term safety and the necessity for standardized characterization methodologies, helping researchers optimize MXene-based nanofluids in many technological fields.